Bintrafusp alfa (M7824), a bifunctional fusion protein targeting TGF-β and PD-L1: results from a phase I expansion cohort in patients with recurrent glioblastoma. Issue 1 (9th April 2021) - Khasraw, Mustafa; Weller, Michael; Lorente, David; Kolibaba, Kathryn; Lee, Chee Khoon; Gedye, Craig; I. de La Fuente, Macarena; Vicente, David; Reardon, David A; Gan, Hui K; Scott, Andrew M; Dussault, Isabelle; et al.
Abstract: Background: For patients with recurrent glioblastoma (rGBM), there are few options following treatment failure with radiotherapy plus temozolomide. Bintrafusp alfa is a first-in-class bifunctional fusion protein composed of the extracellular domain of the TGF-βRII receptor (a TGF-β "trap") fused to a human IgG1 antibody blocking PD-L1. Methods: In this phase I, open-label expansion cohort (NCT02517398), patients with rGBM that progressed after radiotherapy plus temozolomide received bintrafusp alfa 1200 mg Q2W until disease progression, unacceptable toxicity, or trial withdrawal. Response was assessed per RANO criteria. The primary endpoint was disease control rate (DCR); secondary endpoints included safety. Results: As of August 24, 2018, 35 patients received bintrafusp alfa for a median of 1.8 (range, 0.5–20.7) months. Eight patients (22.9%) experienced disease control as assessed by an independent review committee: 2 had a partial response, 4 had stable disease, and 2 had non-complete response/non-progressive disease. Median progression-free survival (PFS) was 1.4 (95% confidence interval [CI], 1.2–1.6) months; 6- and 12-month PFS rates were 15.1% and 11.3%, respectively. Median overall survival (OS) was 5.3 (95% CI, 2.6–9.4) months; 6- and 12-month OS rates were 44.5% and 30.8%, respectively. The DCR (95% CI) was 66.7% (22.3–95.7%) for patients with IDH -mutant GBM ( n = 6) and 13.8% (3.9–31.7%) for patients with IDH –wild-type GBM ( n = 29). Disease control was seen regardless of PD-L1 expression. Twenty-five patients (71.4%) experienced treatment-related adverse events (grade ≥3; 17.1% [ n = 6]). Conclusions: The percentage of patients achieving disease control and the manageable safety profile may warrant further investigation of bintrafusp alfa in GBM.